Melayani dengan Integritas: Etika Pelayanan, Inovasi Harga, dan Pemasaran Digital sebagai Manifestasi Prinsip-Prinsip Ekonomi Islam di Kabupaten Simalungun - Sahdila, Rizki; Ramadhani, Sri; Imsar (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
The telecommunications sector is a pivotal driver of Indonesia’s digital economic growth, particularly amid the rapid adoption of information and communication technologies. CV Digital Satelit Indonesia—a service enterprise specializing in telecommunications equipment repair—has expanded its operations by integrating Islamic economic principles. This study examines how service ethics, innovative pricing, and digital marketing influence business growth within a Sharia-compliant framework. Using a quantitative design, data from 50 purposively selected respondents were analyzed through validity and reliability tests, classical assumption checks, and t- and F-tests. Findings reveal that service ethics and price innovation have a statistically significant, positive impact on business development, while digital marketing shows no significant effect. Service ethics emerged as the strongest predictor (p = 0.001), indicating that delivery grounded in honesty, accountability, and integrity fosters greater trust and loyalty. The limited impact of digital marketing likely stems from promotional content lacking the emotional and spiritual depth needed to convey Islamic values effectively. Collectively, however, all independent variables significantly affect growth, highlighting the strategic value of embedding Sharia principles in service and pricing, alongside refining Islamic-oriented digital marketing to strengthen its persuasive capacity